Age-related differences in the elderly in a spatial recognition task. Issue 10 (26th November 2019) - Tascón, Laura; Castillo, Joaquín; Cimadevilla, José Manuel
ABSTRACT: Spatial memory is a cognitive ability which declines with ageing thus showing changes in some process such as the use of allocentric strategies. These age-related changes in spatial orientation suggest that this skill could be an adequate marker of cognitive decline. Many tasks used in investigation to assess spatial memory demand a participant's active role, which involves that the navigational experience is different for everyone. In this study, the Almeria Spatial Memory Recognition Test (ASMRT), a test based on a recognition paradigm, was used to offer the same experience with the environment. The aim of this research was to determine if the ASMRT is suitable to be applied in the elderly and detect spatial memory differences as one age. The ASMRT and other neuropsychological tests were applied in a sample aged between 50and 79 years. Results revealed a decrease in the ASMRT performance by the older group. No gender differences were found. Performance in attention and visuospatial working memory tests revealed some correlations with the ASMRT performance. In conclusion, this study demonstrates that 70–79-year-old participants clearly show age-related changes in spatial memory. Thanks to its simplicity the ASMRT could be used as a screening test in medical practice.